2004
DOI: 10.1139/b04-074
|View full text |Cite
|
Sign up to set email alerts
|

Lobaria pulmonaria abundance as an indicator of macrolichen diversity in Interior Cedar–Hemlock forests of east-central British Columbia

Abstract: Orographic precipitation over interior mountains has resulted in the formation of the inland temperate rainforest, where certain stands are potentially antique and support a rich flora of epiphytic macrolichens. We documented macrolichen diversity across three age-classes in forests of the Interior Cedar-Hemlock biogeoclimatic zone (i.e., ICHwk3 subzone) east of Prince George, British Columbia. Our objectives were to report changes in lichen communities with stand age, identify potential indicators of antiquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 22 publications
3
72
0
2
Order By: Relevance
“…Species from this genus have been cited as indicators of preserved forest ecosystems and associated with forest areas of high ecological continuity (Campbell andFredeen 2004, Liira andSepp 2009). Their presence is also associated with a variety of other rare or endangered species, and hence they can be considered as umbrella species (Scheidegger andWerth 2009, Nascimbene et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Species from this genus have been cited as indicators of preserved forest ecosystems and associated with forest areas of high ecological continuity (Campbell andFredeen 2004, Liira andSepp 2009). Their presence is also associated with a variety of other rare or endangered species, and hence they can be considered as umbrella species (Scheidegger andWerth 2009, Nascimbene et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used as an indicator species of undisturbed forest ecosystems and forest areas of long ecological continuity (Rose, 1976;Andersson & Appelqvist, 1987;Andersson et al, 2003;Liira & Sepp, 2009). Furthermore, as L. pulmonaria associates with many other rare or endangered lichen species (Campbell & Fredeen, 2004;Pykälä, 2004;Nascimbene et al, 2010) and wood beetles (Nilsson et al, 1995) of old growth forests, it has been used as a flagship or umbrella species for nature conservation (Scheidegger & Werth, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…First, the presence and high abundance of L. pulmonaria across most of our research sites (wet or dry) proved not to be a sensitive indicator to site-specific conditions and lichen diversity (as suggested by Campbell and Fredeen (2004)). This result concurs with Kalwij et al (2005) that suggested that L.pulmonaria at the site level is not sensitive to landscape disturbances, but could be a useful indicator of lichen diversity and disturbance frequencies when comparing among regional landscapes.…”
Section: Discussionmentioning
confidence: 82%
“…Goward and Arsenault (2000) identify some of these forest stands as "antique": sites where the last major stand replacement disturbance event, such as fire, happened well before the current generation of trees established. Preliminary studies (Goward 2003) In the U.S. Pacific Northwest and elsewhere canopy macrolichens have been used as indicators of stand age (Hyvarinen et al 1992, Campbell andFredeen 2004) and environmental conditions on forested landscapes (McCune et.al. 2000, 2002, Liden and Hilmo 2005.…”
Section: Rainforest Landscape Introductionmentioning
confidence: 99%